The Effectiveness of Developing Digital Comic Media in Online Learning at SMK Nusatama Padang - Maswati Maswati; Anni Faridah (Postgraduate School, Universitas Negeri Padang, 2022)
This study aims to improve student learning outcomes on the subject of food safety through the development of digital comic media at SMK Nusatama Padang. This research is development research with a 4-D model. The data in this study are the results of qualitative research given by experts/teachers and students through a given questionnaire. Then the daily test value and practice value. The results showed that: The use of digital comic learning media can improve student learning outcomes by looking at differences in learning outcomes from the pretest and posttest. Posttest learning outcomes are higher than the pretest. Therefore, comic media is recommended for use by teachers in learning food safety.